Cytotoxic and vasogenic cerebral oedema in traumatic brain injury: Assessment with FLAIR and DWI imaging. (November 2014) - Hudak, Anne M.; Peng, Lifang; Marquez de la Plata, Carlos; Thottakara, John; Moore, Carol; Harper, Caryn; McColl, Roderick; Babcock, Evelyn; Diaz-Arrastia, Ramon
Abstract Primary objective: Cerebral oedema is a common complication of traumatic brain injury (TBI). The use of Fluid-Attenuated Inversion Recovery (FLAIR) imaging in combination with Diffusion Weighted Imaging (DWI) has the potential to distinguish between cytotoxic and vasogenic oedema. This study hypothesized a significant relationship between cytotoxic lesion volume and outcome. Research design: This observational study reports on a convenience sample where MRI was obtained for clinical purposes. Methods and procedures: Clinical post-TBI FLAIR and DWI images were analysed. For this study, lesions were defined as primarily cytotoxic oedema if the ratio of FLAIR to DWI lesion volume was comparable, defined as a ratio <2. If the ratio of FLAIR to DWI lesion volume was ≥2, oedema was considered predominantly of vasogenic origin. Main outcomes and results: The sample consisted primarily of males with TBIs whose injury severity ranged from complicated mild to severe. Analysis revealed that both oedema types are common after TBI and both are associated with functional deficits 6 months after injury. Conclusions: Acute MRI may be useful to assess pathology at the tissue after traumatic brain injury. Clinical trials targeting cytotoxic and vasogenic mechanisms of oedema formation may benefit from using DWI and FLAIR MRI as a means to differentiate the predominant oedema type after TBI.